2004
DOI: 10.1158/1078-0432.ccr-04-0850
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Antibody-Dependent Cellular Cytotoxicity of Low-Fucose IgG1 Is Independent of FcγRIIIa Functional Polymorphism

Abstract: Results: We found KM3065-mediated antibody-dependent cellular cytotoxicity was increased 10 to 100-fold compared with rituximab for each of the 20 donors. In contrast to rituximab, KM3065 antibody-dependent cellular cytotoxicity enhancement was similar for both FCGR3A alleles and thus independent of genotype. In addition, antibody-dependent cellular cytotoxicity of both KM3065 and rituximab requires natural killer cells but not monocytes nor polymorphonuclear cells. The antibody-dependent cellular cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
146
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(167 citation statements)
references
References 34 publications
19
146
0
2
Order By: Relevance
“…Previous studies have shown that the FcgRIIIA polymorphism is associated with differential affinity and binding to human IgG1 mAbs. However, in CLL, the FcgR polymorphism did not predict responses to low-fucosylated mAbs, 32,36,37 suggesting that this polymorphism does not explain the variability in degranulation responses. Instead, NK-cell degranulation might be affected by the effector/target ratio, in agreement with Fischer et al 38 Finally, the individual variability might be also attributed to intrinsic resistance of CLL cells to degranulation as observed in 1/21 patients.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that the FcgRIIIA polymorphism is associated with differential affinity and binding to human IgG1 mAbs. However, in CLL, the FcgR polymorphism did not predict responses to low-fucosylated mAbs, 32,36,37 suggesting that this polymorphism does not explain the variability in degranulation responses. Instead, NK-cell degranulation might be affected by the effector/target ratio, in agreement with Fischer et al 38 Finally, the individual variability might be also attributed to intrinsic resistance of CLL cells to degranulation as observed in 1/21 patients.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, it is likely that genotype modulated this relationship through a mechanism other than ADCVI itself. Otherwise, we might expect the high-affinity genotypes (VVs and HHs) to be associated with a lower risk of infection at any given level of serum ADCVI activity because the higher affinity genotypes mediate better ADCC activity (40,41). In contrast, high-affinity genotypes may enhance the risk of infection through an Ab-dependent mechanism, as suggested by the finding that infants homozygous for Fc␥RIIa H have at least a 2.2-fold increased risk of perinatal HIV infection compared with infants having one or no H allele (42).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, modification of the n-glycans attached to the antibody constant region has been employed for enhancing antibody ADCC-mediated activity (95)(96)(97). As nonfucosylated IgGs show stronger affinity for FcγRIIIa binding, superior in vivo efficacy has been demonstrated with nonfucosylated therapeutic antibodies in both animal studies and human clinical trials (98)(99)(100). Therefore, application of QP along with considerations regarding affinity differences and the diversity in the efficiency and potency for the effector systems across species will be of critical significance for the design of effective preclinical safety studies and dose selection across species (5,6,9).…”
Section: Introductionmentioning
confidence: 99%